Motyw antropologiczny w encyklice Benedykta XVI Deus caritas est - Kiejkowski, Paweł (Poznańskie Studia Teologiczne, 2008)
The subject of the article is the theological anthropology which is pointed in the first encyclical „Deus caritas est” written by Pope Benedict XVI. In his encyclical the Holy Father focuses on the most essential „reality” in the Church - Love. He wrote the encyclical as a classic apologetic discourse. The pope dialogues with the non-christian thoughts - the ancient thought and the modem thought (Frederic Nietzsche and Carol Marks). The pope speaks about Love. At the same time, he presents the Christian image of man and man’s vocation. The newness and authentic of Christian love is really connected with the Christian image of Triune God, God who is Love. The radical newness of Christian understanding of God is the groundwork o f understanding the man and man’s vocation. This is the man who lives in - important for his identity - relation to God and another man. The man as „I” realizes in a community „we”. The man „in relation” is the image of God. In the encyclical the vision of man is through theological, christological and trinitarian. It is the vision of man who is called to live in a community (communion). And the vision realizes in the community of Church called community of love.